HUMAN – ENVIRONMENT CONNECTION : THE BRIEF REFLECTION - Wahyu Rahardjo (Jurnal Psikologi, 2006)
Human will not release their dependence from the nature untill now. On the other side, the nature itselfalso has dependency to human even though is not as much as human has. More or less, the humanenvironmental personality effects the way human interact to the nature. Furthermore, human alsodevelop the life that might be has negative consequences to the nature. At this point, controlling thenature destoration should be done in order not to ruin the nature balance.Key words: human-environmental interaction, environmental personality